A Core‐Shell Assembly of Hierarchical Porous Ni@C Nanospheres Synthesized from Metal‐Organic Framework for Electrochemical Energy Application. Issue 9 (6th March 2019) - Kumar, Mohit; Kim, Min Seob; Jeong, Dong In; Humayoun, Usama B.; Yoon, Dae Ho
Abstract : Metal‐organic frameworks (MOFs) have emerged as one of the most outstanding innovated and functional materials for electrochemical application. Here, the structure of novel MOFs‐derived hierarchically porous Nickel@Carbon nanospheres (HP‐Ni@C‐N) synthesized via pyrolysis after the solvothermal reaction is discussed. The method includes the decomposition of the trimesic acid as an organic molecule at a specific temperature of transformation into a carbon matrix wrapping of nickel nanoparticles (Ni NPs). Furthermore, HP‐Ni@C‐N supported on nickel foam as an electrochemical energy storage supercapacitor application and obtained 912 F g −1 at 10 mV s −1 is reported. Interestingly, the covalent bridge between the Ni core and carbon shell facilitates the faster ions transportation. Therefore, it is presumed that this work can be informative and elucidative for the construction of MOFs‐derived transition metals hybrid nanostructures. Abstract : The synthesis of hierarchically porous Nickel@Carbon nanospheres core‐shell structure is constructed using an organic linker (metal‐organic framework) and an inorganic metal salt. The main advantage of metal‐organic framework is to increase the surface area, which is beneficial for improving the electrochemical performance. As synthesized material exhibits a good capacitance of 912 F g −1 at 10 mV s −1 with good stability for 5000 cycles.